Aerobactin-Mediated Iron Acquisition Enhances Biofilm Formation, Oxidative Stress Resistance, and Virulence of Yersinia pseudotuberculosis - Li, Changfu; Pan, Damin; Li, Mengyuan; Wang, Yao; Song, Luting; Yu, Danyang; Zuo, Yuxin; Wang, Kenan; Liu, Yuqi; Wei, Zhiyan; Lu, Zhiqiang; Zhu, Lingfang; et al. (Frontiers in Microbiology, 2021)
Aerobactin is a citrate-hydroxamate siderophore that is critical for the virulence of pathogenic enteric bacteria. However, although the aerobactin-producing iucABCD-iutA operon is distributed widely in the genomes of Yersinia species, none of the pathogenic Yersinia spp. was found to produce aerobactin. Here, we showed that the iucABCD-iutA operon in the food-borne enteric pathogen Yersinia pseudotuberculosis YPIII is a functional siderophore system involved in iron acquisition. And expression of the operon was found to be directly repressed by the ferric uptake regulator (Fur) in an iron concentration dependent manner. In addition, we demonstrated that the aerobactin-mediated iron acquisition contributes to bacterial growth under iron-limited conditions. Moreover, we provided evidence that aerobactin plays important roles in biofilm formation, resistance to oxidative stress, ROS removal and virulence of Y. pseudotuberculosis. Over all, our study not only uncovered a novel strategy of iron acquisition in Y. pseudotuberculosis, but also highlighted the importance of aerobactin in the pathogenesis of Y. pseudotuberculosis.